The July 2015 Debris flow in Barsem, Western Pamir (GBAO) Tajikistan: Description and causes - Zafar Avzalshoev; Uchimura Taro (E3S Web of Conferences, 2023)
Tajikistan is a landlocked country in the Central Asia republics of the former Soviet Union. Tajikistan is prone to many natural disasters. Most commonly in Tajikistan, mudflows occur in the South and North parts of the country. The 2015 Barsem mudflow caused significant damage to the entire village, a territory of the Western Pamir Gorno-Badakhshan Autonomous Region (GBAO), Tajikistan; fortunately, no human casualties. The total volume of debris flow is about 4.9 million m3. Typically, precipitation above 15-20mm per day in arid areas causes mudflow. Accumulated water during the intensive melting of the glacier and snowfields was saturated with water by the moraine sediment blocking its paths (which served as a dam for the lake that formed). Several studies indicate that mudflow triggers excess pore pressure or liquefaction of the soil; consequently, sudden and high shear resistance losses eventually generate a mudflow [5][6]. Although mudflows and landslides occur annually, after the 2015 Barsem mudflow, it becomes clear that the intensity and frequency of new events are increasing. Consequently, the author strongly believes establishing and implementing an early warning system can be essential.